An alternative dietary strategy to make weight while improving mood, decreasing body fat, and not dehydrating: A case study of a professional jockey - Wilson, G.; Chester, N.; Eubank, M.; Crighton, B.; Drust, B.; Morton, J. P.; Close, G. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
Professional jockeys are unique among weight-making athletes, as they are often required to make weight daily and, in many cases, all year-round. Common methods employed by jockeys include dehydration, severe calorie restriction, and sporadic eating, all of which have adverse health effects. In contrast, this article outlines a structured diet and exercise plan, employed by a 22-yr-old professional National Hunt jockey in an attempt to reduce weight from 70.3 to 62.6 kg, that does not rely on any of the aforementioned techniques. Before the intervention, the client`s typical daily energy intake was 8.2 MJ (42% carbohydrate [CHO], 36% fat, 22% protein) consumed in 2 meals only. During the 9-wk intervention, daily energy intake was approximately equivalent to resting metabolic rate, which the athlete consumed as 6 meals per day (7.6 MJ, 46% CHO, 19% fat, 36% protein). This change in frequency and composition of energy intake combined with structured exercise resulted in a total body-mass loss of 8 kg, corresponding to reductions in body fat from 14.5% to 9%. No form of intentional dehydration occurred throughout this period, and mean urine osmolality was 285 mOsm/kg (SD 115 mOsm/kg). In addition, positive changes in mood scores (BRUMS scale) also occurred. The client was now able to ride light for the first time in his career without dehydrating, thereby challenging the cultural practices inherent in the sport.